Interannual Variations in Winter Precipitation in Northern East Asia - Yuchi Zhang; Tianjiao Ma; Yuehua Li; Wen Chen (Water, 2025)
Winter precipitation (P) in East Asia (EA) is characterized by a wetter south and a drier north. Most of the existing research has concentrated on elucidating the mechanisms of winter P in southern EA, with relatively less attention given to northern East Asia (NEA). Our analysis showed that the correlation coefficient (c.c.) of average winter precipitation anomaly percentage (PAP) between southern EA and NEA is 0.24 for the period 1950–2023, indicating substantial regional difference. An empirical orthogonal function (EOF) analysis was conducted on the winter PAP in NEA. The first and second mode (EOF1 and EOF2) account for 45.5% and 17.9% of the total variance, respectively. EOF1 is characterized by a region-wide uniform spatial pattern whereas EOF2 exhibits a north–south dipole pattern. Further analysis indicated that the two EOF modes are related to distinct atmospheric circulation and external forcings. Specifically, EOF1 is linked to a wave train from Central Siberia toward Japan, while EOF2 is connected with an anomaly similar to the Western Pacific pattern. Variations in mid–high latitude sea surface temperatures, sea ice, and snow are potential factors influencing EOF1. EOF2 exhibits a close relationship with tropical SST anomalies.